2000
DOI: 10.1038/72945
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment induces structural changes and recovery from nonspatial memory deficits in CA1 NMDAR1-knockout mice

Abstract: We produced CA1-specific NMDA receptor 1 subunit-knockout (CA1-KO) mice to determine the NMDA receptor dependence of nonspatial memory formation and of experience-induced structural plasticity in the CA1 region. CA1-KO mice were profoundly impaired in object recognition, olfactory discrimination and contextual fear memories. Surprisingly, these deficits could be rescued by enriching experience. Using stereological electron microscopy, we found that enrichment induced an increase of the synapse density in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
452
7
7

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 694 publications
(502 citation statements)
references
References 37 publications
36
452
7
7
Order By: Relevance
“…Further, we found that the improving effects of galantamine were prevented by SCH-23390, a dopamine-D1 receptor antagonist, and sulpiride, a dopamine-D2 receptor antagonist. Taken together, our results suggest that these hippocampus-dependent performance in these tasks were impaired by Ab 25À35 infusion as the result of failure of nAChR and dopamine responses, as the hippocampus is involved in the object recognition behavior (Rampon et al, 2000;Hammond et al, 2004) and the contextual fear conditioning (Daumas et al, 2004). These findings provide the first in vivo evidence that galantamine augments dopaminergic neurotransmission within the hippocampus through the allosteric activation of nAChR.…”
Section: Discussionmentioning
confidence: 52%
“…Further, we found that the improving effects of galantamine were prevented by SCH-23390, a dopamine-D1 receptor antagonist, and sulpiride, a dopamine-D2 receptor antagonist. Taken together, our results suggest that these hippocampus-dependent performance in these tasks were impaired by Ab 25À35 infusion as the result of failure of nAChR and dopamine responses, as the hippocampus is involved in the object recognition behavior (Rampon et al, 2000;Hammond et al, 2004) and the contextual fear conditioning (Daumas et al, 2004). These findings provide the first in vivo evidence that galantamine augments dopaminergic neurotransmission within the hippocampus through the allosteric activation of nAChR.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, Apoe -/-and wild-type mice have similar levels of H 1 expression and a similar affinity for H 1 -specific ligands in the amygdala, hypothalamus, hippocampus, and cortex. These data indicate that there is no simple association between levels of H 1 and H 3 receptor expression in structures associated with anxiety vs cognition which could explain why H 3 antagonists impaired hippocampusand cortex-dependent novel object recognition (Rampon et al, 2000) but did not increase more amygdala-dependent measures of anxiety in the plus maze or why Apoe -/-mice were more sensitive to the anxiety-reducing effects of mepyramine. Interestingly, in young Apoe -/-mice the enhancement of the a-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptors by phosphatidylserine (PS) was abolished without genotype changes in AMPA receptor binding (Valastro et al, 2001).…”
Section: Discussionmentioning
confidence: 86%
“…Novel object recognition was used to evaluate nonspatial learning and memory, as described (Raber et al, 2002) according to Rampon et al (2000). On each of 3 consecutive days, the mice were habituated to a Plexiglas enclosure (16 Â 16 inches, open from the top) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pioneering observation generated a large number of studies, which have shown significant differences in animals' behavior associated with enriched living conditions. Environmental enrichment in rats leads to better performance in various learning tasks (eg Greenough et al, 1972;Mohammed et al, 1990;Nilsson et al, 1999;Rampon et al, 2000), enhanced social play behavior (Morley-Fletcher et al, 2003), increased exploration, lower anxiety, and ameliorated plasma corticosterone response to stress (Levine, 1962(Levine, , 1967. Experiments have shown that improvements in behavioral performances were accompanied with changes in various neurochemical and anatomical features in rat brains.…”
Section: Introductionmentioning
confidence: 99%